Does the Disposition Effect Justify the Options Traders’ Irrationality? - V. Choubey; P. V. Joshi (Финансы: теория и практика, 2024)
The options trader’s decisions are expected to be rational decisions but an element of irrationality is observed in decision making. The Disposition effect is the behavioral aspect of an investor which explains his irrational decision-making. The disposition effect is the tendency to keep losing positions too long and selling winning positions too early. The present research work studies the disposition effect in options trading. Options are derivatives of underlying assets which give the holder the right to exercise them at a given date and price. In this research work, elements of disposition effect namely,Herding (HE), Mental accounting (MA), Risk Aversion (RA) are studied along with Trade enablers (TE) and Cost consciousness (CC). The data was collected from 250 respondents’ trading options on the National Stock Exchange, India. The collected data was analyzed using Structured Equation Modeling (SEM). The results reflected that the disposition effect existed in decision-making by options traders. Trade Enabler consisting of Time decay and Open Interest, and Herding emerged as significant elements of disposition effect for options trading. Mental accounting, risk aversion, and cost-consciousness emerged as less significant elements affecting the disposition effect in options trading.